SERUM LEVELS OF SOLUBLE CD50 ANTIGEN AND CONTENTS OF CD50-POSITIVE MONONUCLEAR CELLS IN THE PATIENTS WITH BURNS - A. A. Babaev (SPb RAACI, 2014)
Abstract. A decrease in relative contents of CD50+-mononuclear cells and elevated serum levels of soluble CD50 antigen have been revealed in blood of the burn patients with different areas of skin lesions. The changes observed may influence the development of immunodeficiency which arises as a result of the burn trauma.